The Economic Dynamics of Inflation and Unemployment - Tamara Todorova (Theoretical Economics Letters, 2012)
We study the time path of inflation and unemployment using the Blanchard treatment of the relationship between the two and taking the monetary policy condition into account. We solve the model both in continuous and discrete time and compare the results. The economic dynamics of inflation and unemployment shows that they fluctuate around their intertemporal equilibria, inflation around the growth rate of nominal money supply, respectively, and unemployment around the natural rate of unemployment. However, while the continuous-time case shows uniform and smooth fluctuation for both economic variables, in discrete time their time path is explosive and nonoscillatory. The hysteresis case shows dynamic stability and convergence for inflation and unemployment to their intertemporal equilibria both in discrete and continuous time. When inflation affects unemployment adversely the time paths of the two, both in discrete and continuous time, are dynamically unstable.
Keywords: E23; E51; 330; economic dynamics; Phillips curve; inflation; unemployment